National Media, Sports Rivalry, and Framing Practices: Indonesia–Malaysia Football Coverage - Salshabila Khairunnisa; Eko Hero; Bunga Astini (COMMICAST, 2025)
This study aims to analyse how the Indonesian and Malaysian state-owned national media frame the Indonesia–Malaysia football rivalry and how this framing contributes to the construction of competitive nationalism. The object of this study is the Indonesian–Malaysian football news published by Antara News (Indonesia) and Bernama (Malaysia) from 2019 to May 2025. This study uses a qualitative method with Robert M. Entman's framing model analysis approach, which includes four elements, namely defining problems, diagnosing causes, moral judgement, and treatment recommendations. The research data consists of a corpus of online news related to football matches and conflicts between supporters related to the Indonesia-Malaysia rivalry. Data analysis was conducted through systematic coding using NVivo 14 software to identify dominant framing patterns. The results show that both media outlets predominantly emphasised the elements of defining problems and diagnosing causes, framing football rivalry as a competitive dynamic fraught with conflict. Antara News tended to diagnose the causes of conflict by highlighting the actions of the opposing party, while Bernama placed more emphasis on technical factors of the match and the emotional responses of supporters. The element of moral judgement was used to legitimise the national position of each country, as well as to provide recommendations for dealing with reactive conflicts. This study contributes to media studies, particularly framing, by highlighting comparisons between the national media of Indonesia and Malaysia in their coverage of Indonesian-Malaysian football rivalry. This study emphasises the need for balanced journalistic practices oriented towards conflict management in cross-border sports coverage and the adoption of approaches to prevent conflict escalation.